The use of portfolios as a teaching and learning instrument in research methods in education (Revista Lusófona de Educação, 2025)
Adopting an active learning paradigm, combined with a critical-reflective approach and direct studentengagement in research tasks, has been widely advocated for teaching research methods in higher education (Matos et al., 2023a; São José, 2020). This article reflects on a pedagogical experience within a master degree in Education, which incorporated the development of portfolios containing various research activities. Through the analysis of the students’ work and their responses to a questionnaire, we examine the potential of this tool in the teaching and learning of research methods. The portfolio’s role in enhancing and diversifying the learning trajectory is emphasized, fostering reflection on the acquired knowledge and skills and underscoring responsibility in knowledge construction.Furthermore, the progressive feedback mechanism is particularly significant for improving learning outcomes, ensuring students’ motivation and resilience.